Efficacy of psychosocial interventions for survivors of intimate partner violence: protocol for a systematic review and meta-analysis - Hannah M. Micklitz; Carla M. Glass; Jürgen Bengel; Lasse B. Sander (BJPsych Open, 2023)
Survivors of intimate partner violence (IPV) are at risk for serious health consequences, and providing effective psychosocial interventions to support these individuals is a major global health challenge. Previous systematic reviews and meta-analyses in this field do not allow for clear conclusions about the efficacy of these interventions, owing to a narrow focus on specific subpopulations or intervention formats. This protocol presents a systematic review and meta-analysis, which will provide a comprehensive overview of the empirical evidence of various psychosocial interventions for survivors of IPV and investigate their efficacy in improving safety-related, mental health and psychosocial outcomes both overall and within homogeneous subgroups (trial registration: https://osf.io/4gp95). We will systematically search the literature databases PsycInfo, MEDLINE, Embase and CENTRAL. Randomised controlled trials evaluating the efficacy of psychosocial interventions in increasing the safety or mental health of IPV survivors compared with a control group will be eligible. We will extract relevant data from eligible studies and assess study quality using the Cochrane Risk of Bias 2 (RoB 2) tool. We will qualitatively summarise the results and we will calculate weighted effect sizes under random effect model assumption for the primary outcomes IPV, depression and post-traumatic stress disorder. We will perform subgroup analyses to investigate the moderating effects of theoretical basis, delivery mode, intensity and setting of psychosocial interventions. The resultant overview of the current body of evidence for psychosocial interventions for IPV survivors is intended to inform future research and practice.